2008
DOI: 10.1016/j.cropro.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Lagomorph and rodent responses to two protein hydrolysates

Abstract: Various species of rodents and lagomorphs were used in bioassays to determine the effectiveness of protein hydrolysates (specifically hydrolyzed casein and gelatin) as herbivore repellents. Mixed sex groups of captive rabbits, pocket gophers, voles, and mountain beavers were offered hydrolyzed casein or gelatin test diets in single-choice tests following a training period with a hydrolysate-free diet. The effectiveness of either hydrolyzed casein or gelatin was dependent on the species. Hydrolyzed casein was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Blood and egg are further examples of repellent ingredients that do not cause pain or malaise yet are effective herbivore repellents . Hydrolyzed casein (HC) is a similar animal-based stimulus that produces long-lived avoidance in a variety of herbivores (Kimball & Nolte 2006;Figueroa et al 2008). These animalbased ingredients are non-toxic (i.e.…”
Section: Altering Palatability With Repellentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood and egg are further examples of repellent ingredients that do not cause pain or malaise yet are effective herbivore repellents . Hydrolyzed casein (HC) is a similar animal-based stimulus that produces long-lived avoidance in a variety of herbivores (Kimball & Nolte 2006;Figueroa et al 2008). These animalbased ingredients are non-toxic (i.e.…”
Section: Altering Palatability With Repellentsmentioning
confidence: 99%
“…are the most common source of damage, most commercial repellent products are marketed to reduce deer browse. However, repellents may affect other mammals (Nolte & Wagner 2000;Figueroa et al 2008). In general, repellents have short-term effects and are influenced by numerous factors such as animal density, food availability, and climatic conditions (e.g., temperature extremes, rainfall).…”
Section: Repellent Use In Practicementioning
confidence: 99%
“…Casein hydrolysate is also avoided by mice, which may be a useful model for understanding the mechanisms of hydrolyzed casein rejection. The avoidance of protein hydrolysates by these animals is not nutritionally driven, but is actually the result of a factor within the protein that these animals find unpalatable [43]. In fact, animals should choose hydrolyzed casein-containing foods over casein-containing foods when nutritionally compromised, due to its shorter gastrointestinal transit time and increased rate of amino acid adsorption compared to intact casein [44].…”
Section: Bitter Peptides In Protein Hydrolysatesmentioning
confidence: 99%
“…In spite of numerous efforts to apply laboratory‐derived vole repellents in plant protection, a successful field application method is still considered to be difficult owing to the fossorial behaviour of the target species . Further studies have therefore focused on the appropriate formulation of the identified plant metabolites/combinations to achieve a long‐lasting repelling effect underground once applied into the burrow openings.…”
Section: Discussionmentioning
confidence: 99%